Endothelial progenitor cells stimulate neonatal lung angiogenesis through FOXF1-mediated activation of BMP9/ACVRL1 signaling - Wang, Guolun; Wen, Bingqiang; Deng, Zicheng; Zhang, Yufang; Kolesnichenko, Olena A.; Ustiyan, Vladimir; Pradhan, Arun; Kalin, Tanya V.; Kalinichenko, Vladimir V. (Nature communications, 2022)
Pulmonary endothelial progenitor cells (EPCs) are critical for neonatal lung angiogenesis and represent a subset of general capillary cells (gCAPs). Molecular mechanisms through which EPCs stimulate lung angiogenesis are unknown. Herein, we used single-cell RNA sequencing to identify the BMP9/ACVRL1/SMAD1 pathway signature in pulmonary EPCs. BMP9 receptor, ACVRL1, and its downstream target genes were inhibited in EPCs from Foxf1 WT/S52F mutant mice, a model of alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV). Expression of ACVRL1 and its targets were reduced in lungs of ACDMPV subjects. Inhibition of FOXF1 transcription factor reduced BMP9/ACVRL1 signaling and decreased angiogenesis in vitro. FOXF1 synergized with ETS transcription factor FLI1 to activate ACVRL1 promoter. Nanoparticle-mediated silencing of ACVRL1 in newborn mice decreased neonatal lung angiogenesis and alveolarization. Treatment with BMP9 restored lung angiogenesis and alveolarization in ACVRL1-deficient and Foxf1 WT/S52F mice. Altogether, EPCs promote neonatal lung angiogenesis and alveolarization through FOXF1-mediated activation of BMP9/ACVRL1 signaling. The molecular mechanisms through which pulmonary endothelial progenitor cells stimulate lung angiogenesis are not clear. Here, authors show that these cells stimulate the growth of alveolar capillaries and alveoli of newborn mice through FOXF1 and FLI1 nuclear protein-activation of the BMP9/ACVRL1/SMAD1 signaling pathway.